THE ROLE OF SMALL AND MEDIUM-SIZED ENTERPRISES WITHIN THE FRAMEWORK OF POST-WAR SOCIO-ECONOMIC RECOVERY INSTRUMENTS FOR RURAL AREAS - Kachula, Svitlana; Lastovchenko, Pavlo (Sworld-Us Conference proceedings, 2025)
The study explores the role of small and medium-sized enterprises (SMEs) in the post-war socio-economic recovery of rural areas in Ukraine. Theoretical and methodological approaches to analyzing SMEs as drivers of local development are substantiated. Stra